2021
DOI: 10.3390/ijerph18031057
|View full text |Cite
|
Sign up to set email alerts
|

The Bench Press Grip Width Does Not Affect the Number of Repetitions Performed at Different Velocity Loss Thresholds

Abstract: This study aimed (I) to compare the number of repetitions that can be completed to failure (XRM) and before reaching a 15%, 30%, or 45% velocity loss threshold (XVLT) in the bench press exercise performed using different grip widths, and (II) to examine the inter-individual variability in the percentage of completed repetitions with respect to the XRM when the set volume is prescribed based on a fixed number of repetitions (FNR) and several velocity loss thresholds (VLT). Nineteen men performed four separate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 36 publications
(75 reference statements)
4
11
0
Order By: Relevance
“…The discrepancy between studies may be attributed to certain methodological differences, such as the load adjustment method (% 1RM vs. velocity obtained from general or individual load-velocity relationships), velocity variable (mean velocity vs. mean propulsive velocity), or execution mode (touch-and-go technique vs. concentric-only technique from the bar holders or chest). Furthermore, the present findings are in line with previous studies (6,19,24) that have observed a comparable interindividual variability for the %Rep completed for a given %VL (between-subjects CV = 2.9–31.3%) and the actual number of repetitions that can be completed to failure against a given relative load (between-subjects CV = 8.6–38.5%). The high interindividual variability generally reported for the %Rep associated with different %VL suggests that implementing the same magnitude of %VL for all subjects does not ensure a homogeneous level of effort across individuals.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The discrepancy between studies may be attributed to certain methodological differences, such as the load adjustment method (% 1RM vs. velocity obtained from general or individual load-velocity relationships), velocity variable (mean velocity vs. mean propulsive velocity), or execution mode (touch-and-go technique vs. concentric-only technique from the bar holders or chest). Furthermore, the present findings are in line with previous studies (6,19,24) that have observed a comparable interindividual variability for the %Rep completed for a given %VL (between-subjects CV = 2.9–31.3%) and the actual number of repetitions that can be completed to failure against a given relative load (between-subjects CV = 8.6–38.5%). The high interindividual variability generally reported for the %Rep associated with different %VL suggests that implementing the same magnitude of %VL for all subjects does not ensure a homogeneous level of effort across individuals.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it is plausible to observe a slightly lower interindividual variability for the maximal number of repetitions that can be completed to failure when loads are prescribed from the individual load-velocity relationship (8,24). Finally, in line with previous studies (6–8,19,22,24), the use of a Smith machine, which restricts the movement of the barbell to the vertical direction, may have limited the ecological validity of our results for athletes using free weights in their training programs. Future studies should examine the pattern of repetition velocity decline during training sets to failure with free-weight exercises, but a greater accuracy of velocity recordings for the free-weight variants of the exercises examined above is unlikely.
Practical Applications
The individual %Rep-%VL relationships present a better fit than the general %Rep-%VL relationships when they are determined in sets of the Smith machine prone bench pull exercise performed to failure against different loads.
…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations